Neuronal AChE splice variants and their non‐hydrolytic functions: redefining a target of AChE inhibitors?. (15th October 2013) - Zimmermann, M
<x xml:space="preserve">Abstract</x> AChE enzymatic inhibition is a core focus of pharmacological intervention in Alzheimer's disease (AD). Yet, AChE has also been ascribed non‐hydrolytic functions, which seem related to its appearance in various isoforms. Neuronal AChE presents as a tailed form (AChE‐T) predominantly found on the neuronal synapse, and a facultatively expressed readthough form (AChE‐R), which exerts short to medium‐term protective effects. Notably, this latter form is also found in the periphery. While these non‐hydrolytic functions of AChE are most controversially discussed, there is evidence for them being additional targets of AChE inhibitors. This review aims to provide clarification as to the role of these AChE splice variants and their interplay with other cholinergic parameters and their being targets of AChE inhibition: AChE‐R is particularly involved in the mediation of (anti‐)apoptotic events in cholinergic cells, involving adaptation of various cholinergic parameters and a time‐dependent link to the expression of neuroprotective factors. The AChE‐T C‐terminus is central to AChE activity regulation, while isolated AChE‐T C‐terminal fragments mediate toxic effects via the α7 nicotinic acetylcholine receptor. There is direct evidence for roles of AChE‐T and AChE‐R in neurodegeneration and neuroprotection, with these roles involving AChE as a key modulator of the cholinergic system: in vivo data further encourages the use of AChE inhibitors in the treatment of neurodegenerative conditions such as AD since effects on both enzymatic activity and the enzyme's non‐hydrolytic functions can be postulated. It also suggests that novel AChE inhibitors should enhance protective AChE‐R, while avoiding the concomitant up‐regulation of AChE‐T.